Resin composition, resin composition for recovery aid, use of resin composition in recovery aid, recovery aid, regrind layer, multilayer structure, package, food packaging, and method for producing recovery aid
By using carbon-14 containing EVA with ethylene content over 60 mol% and additives, the resin composition addresses compatibility issues with EVOH and polyolefins, enhancing thermal stability and color suppression in recycled products.
Patent Information
- Application Number
- JP2024120732
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-27
- Filing Date
- 2024-07-26
- Publication Date
- 2025-02-06
AI Technical Summary
Existing resin compositions containing ethylene-vinyl alcohol copolymers (EVOH) and polyolefins face compatibility issues during recycling, leading to poor quality of the recycled products due to their incompatibility, which results in deterioration of physical properties.
Incorporating ethylene-vinyl acetate copolymers (EVA) with an ethylene content of more than 60 mol% and containing carbon-14, along with additives like hydrotalcites and higher fatty acid metal salts, to enhance thermal stability and compatibility.
The resin composition exhibits improved thermal stability and color suppression, maintaining consistent quality even when recycled, making it suitable for use in molded bodies and multi-layer structures.
Smart Images

Figure 2025019035000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition, a resin composition for a recovery aid, use in a recovery aid, a recovery aid, a regrind layer, a multilayer structure, a package, a food package, and a method for producing the recovery aid. [Background technology]
[0002] Conventionally, ethylene-vinyl alcohol copolymers (hereinafter referred to as "EVOH") having an ethylene content of 60 mol% or less have been mainly used as food packaging materials because of their excellent gas barrier properties and transparency. Although sheets, films, etc. used as the food packaging materials can be produced using the above-mentioned EVOH alone, they are often mixed with other thermoplastic resins to improve physical properties, or multilayer structures in which layers made of polyolefin resins, etc. are laminated to impart other functions are used.
[0003] Recently, in order to reduce the environmental load, used resin products, resin scraps and ends generated during the manufacturing process of resin products, and defective products have been collected and recycled into resin compositions containing EVOH and polyolefins.
[0004] However, since EVOH and polyolefins have poor compatibility, there is a problem that the compatibility between EVOH and polyolefins becomes poor during recycling, resulting in a deterioration in the quality of the resin composition and the molded article thereof. In order to solve the above problems, a resin composition containing ethylene-vinyl acetate copolymer (hereinafter referred to as "EVA") and a saponified EVA having an ethylene content of more than 60 mol% has been proposed as a modifying resin composition to be added when producing the above resin composition from recycled materials (see Patent Document 1 below).
[0005] On the other hand, a resin composition containing EVA derived from biomass resources has been proposed as a resin composition that has reduced carbon emissions compared to materials produced using only fossil fuel sources (see Patent Document 2 below). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2009 / 041440 [Patent Document 2] Special Publication No. 2021-536526 Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a resin composition which is excellent in thermal stability and is suppressed in discoloration. [Means for solving the problem]
[0008] However, as a result of intensive research conducted by the present inventors in order to solve the above problems, it has been found that in a resin composition containing EVA and a saponified EVA, the EVA and / or the saponified EVA has a carbon number of 14 ( 14 It has been found that the above problems can be solved by using a material containing C (radioactive carbon-14, half-life 5730 years).
[0009] That is, the present invention has the following aspects. [1] A resin composition containing EVA (A), A resin composition, wherein the EVA (A) contains carbon-14. [2] A resin composition comprising EVA (A) and a saponified EVA having an ethylene content of more than 60 mol% (B), A resin composition, wherein the EVA (A) and / or the saponified EVA (B) contains 14 carbon atoms. [3] The resin composition according to [2], wherein the ethylene-vinyl acetate copolymer (A) contains 14 carbon atoms. [4] The resin composition according to [2], wherein the EVA (A) and / or the saponified EVA having an ethylene content of more than 60 mol% (B) have a bio-based content of 1 to 100%. [5] The resin composition according to any one of [1] to [4], wherein the EVA (A) has a bio-based content of 1 to 100%. [6] The resin composition according to any one of [1] to [4], wherein the EVA (A) has a bio-based content of 40 to 100%. [7] The resin composition according to any one of [1] to [6], wherein the ethylene content of the EVA (A) is 60 to 98 mol %. [8] The resin composition according to any one of [1] to [7], further comprising a hydrotalcite (C). [9] The resin composition according to any one of [1] to [8], further comprising a higher fatty acid metal salt (D).
[10] The resin composition according to [9], wherein the higher fatty acid metal salt (D) is at least one selected from the group consisting of higher fatty acid calcium salts, higher fatty acid magnesium salts, and higher fatty acid zinc salts.
[11] The resin composition according to any one of [1] to
[10] , further comprising a titanium compound (E).
[12] The resin composition according to
[11] , wherein the titanium compound (E) is titanium oxide.
[13] A resin composition for use as a recovery aid, comprising the resin composition according to any one of [1] to
[12] .
[14] Use of the resin composition according to any one of [1] to
[12] as a recovery aid.
[15] A recovery aid comprising the resin composition according to any one of [1] to
[12] .
[16] A regrind layer comprising the recovery aid described in
[15] .
[17] A multi-layer structure comprising a regrind layer as described in
[16] .
[18] The multilayer structure according to
[17] , further comprising a layer containing a polyolefin resin (but not containing EVA (A)).
[19] The multilayer structure according to
[18] , further comprising an adhesive resin layer (excluding EVA(A)) different from the regrind layer.
[20] A packaging material comprising the multilayer structure according to any one of
[17] to
[19] .
[21] Food packaging comprising the multilayer structure according to any one of
[17] to
[19] .
[22] A method for producing a polyester resin composition comprising the steps of: mixing EVA (A) and a saponified EVA having an ethylene content of more than 60 mol% (B); A method for producing a recovery aid, wherein the EVA (A) and / or the saponified EVA (B) contains carbon-14. Effect of the Invention
[0010] The resin composition of the present invention, which is a resin composition containing EVA or a resin composition containing EVA and a saponified EVA, is excellent in thermal stability and coloration suppression, and therefore the resin composition of the present invention can be suitably used as a raw material for molded articles and multilayer structures that are excellent in thermal stability and coloration suppression. Furthermore, the resin composition of the present invention can be suitably used as a recovery aid for increasing the thermal stability of a recycled composition and maintaining a certain level of quality when used resin products containing polyolefin resin and EVOH (ethylene content of 60 mol% or less) or resin scraps discarded during the manufacturing process are recovered and recycled. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in more detail below based on embodiments of the present invention, but the present invention is not limited to the following embodiments.
[0012] In this specification, when the expression "x to y" (x and y are arbitrary numbers) is used, unless otherwise specified, it includes the meaning of "greater than x and less than y", as well as "preferably greater than x" or "preferably smaller than y". In addition, when it is expressed as "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the intention that "it is preferably greater than X" or "it is preferably less than Y". Furthermore, "X and / or Y (X and Y are optional)" means at least one of X and Y, and means the following three cases: X only, Y only, and X and Y. In this specification, the term "film" also includes the terms "tape" and "sheet." In the present specification, the upper limit or lower limit of a numerical range described in stages can be arbitrarily combined with the upper limit or lower limit of a numerical range of another stage. In addition, in the numerical range described in this specification, the upper limit or lower limit of the numerical range can be replaced with a value shown in the examples.
[0013] A resin composition according to one embodiment of the present invention (hereinafter referred to as "the resin composition") is either a resin composition containing EVA (A), wherein the EVA (A) contains 14 carbon atoms, or a resin composition containing EVA (A) and a saponified EVA (B) having an ethylene content of more than 60 mol%, wherein the EVA (A) and / or the saponified EVA (B) having an ethylene content of more than 60 mol% contains 14 carbon atoms. Since the present resin composition is suitable for use as a recovery aid, it can be used as a resin composition for a recovery aid (hereinafter referred to as "the present resin composition for a recovery aid"). Each component will be described below.
[0014] <EVA(A)> The term "EVA" in the EVA (A) used in the present resin composition refers to a polymer obtained by copolymerizing ethylene and vinyl acetate. In the present resin composition, the EVA (A) and / or the saponified EVA (B) having an ethylene content of more than 60 mol% contains carbon-14, and it is particularly preferable that the EVA (A) contains carbon-14.
[0015] EVA containing carbon-14 refers to EVA obtained by chemical or biological synthesis using renewable biomass resources (hereinafter sometimes referred to as "bio-EVA"). Bio-EVA has the characteristic that even if it is incinerated, it does not increase the carbon dioxide concentration in the atmosphere due to the carbon neutrality of biomass.
[0016] The carbon in petroleum-based EVA does not contain carbon-14, whereas bio-EVA does. 14The C concentration can be measured by accelerator mass spectrometry and used as an indicator of the presence or absence of bio-EVA or the content rate (bio-based degree).
[0017] The bio-EVA is preferably made from a plant material among biomass resources, and for example, it is preferable to use ethylene derived from a plant material derived from bioalcohol or vinyl acetate derived from a biomass resource. That is, the EVA containing carbon-14 is preferably made from a plant material.
[0018] The bio-based content can be measured, for example, by the following method. The sample to be measured is burned to generate carbon dioxide, which is then purified in a vacuum line and reduced with hydrogen using iron as a catalyst to generate graphite. The graphite is then subjected to a tandem accelerator-based 14 Attach it to the C-AMS dedicated device (manufactured by NEC) 14 Counting C, 13 Concentration of C ( 13 C / 12 C). 14 Concentration of C ( 14 C / 12 C), and from this measurement, the carbon content of the sample relative to the standard modern carbon is 14 Calculate the percentage of C concentration.
[0019] The bio-based content of the EVA (A) used in the present resin composition is usually 1 to 100%, preferably 5 to 100%, more preferably 10 to 100%, further preferably 40 to 100%, and particularly preferably 60 to 90%. By setting the bio-based content of the bio-EVA (A) within the above range, a resin composition having better thermal stability can be obtained.
[0020] The reason why this resin composition has excellent thermal stability and coloration suppression is that it contains carbon-14( 14 It is believed that this is because bio-EVA containing carbon-14 has stronger bond energy due to the primary isotope effect compared to petroleum-derived EVA that does not contain carbon-14, which slows down decomposition and increases thermal stability and color inhibition.
[0021] The ethylene content in the EVA (A) is usually 1 to 99 mol%, preferably 60 to 98 mol%, and more preferably 70 to 95 mol%. That is, when the ethylene content is equal to or more than the lower limit, the resin composition tends to have excellent thermal stability and extrusion moldability, and when the ethylene content is equal to or less than the upper limit, the resin composition tends to have excellent coloration suppression properties.
[0022] The vinyl acetate content in the EVA (A) is usually 1 to 60 mol%, preferably 2 to 40 mol%, and more preferably 3 to 30 mol%. That is, when the vinyl acetate content is equal to or more than the lower limit, the resin composition tends to have excellent coloring inhibition properties, and when the vinyl acetate content is equal to or less than the upper limit, the resin composition tends to have excellent thermal stability and extrusion moldability.
[0023] The melt flow rate (MFR) of the EVA (A) (190°C, load 2160g) is usually 0.1 to 100g / 10min, more preferably 0.5 to 50g / 10min, and particularly preferably 1 to 30g / 10min. When the MFR is within the above range, dispersibility in other resins when mixed with other resins is improved, and the effects of the present invention tend to be easily exhibited. The MFR can be measured in accordance with JIS K7120.
[0024] The EVA (A) may be a modified product containing a carboxy group obtained by chemically bonding an unsaturated carboxylic acid or an anhydride thereof by addition reaction, graft reaction, or the like, within the scope of the present invention. The amount of such modification is preferably 10 mol% or less, specifically. Examples of the unsaturated carboxylic acid or anhydride thereof include ethylenically unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, ethacrylic acid, and crotonic acid, and ethylenically unsaturated dicarboxylic acids such as fumaric acid, itaconic acid, citraconic acid, maleic acid, monomethyl maleate, monoethyl maleate, and maleic anhydride, and their anhydrides and half esters, among which maleic anhydride is preferably used.
[0025] The EVA (A) may be used alone or in combination of two or more bioEVAs differing in ethylene content, molecular weight, MFR, density, modifying group, modification amount, etc. The EVA (A) may be a petroleum-derived EVA. Furthermore, the EVA (A) may be a petroleum-derived EVA in which part of the carbon is replaced with carbon-14.
[0026] The content of the EVA (A) in the resin composition is usually 1 to 99 mass%, preferably 10 to 98 mass%, more preferably 30 to 97 mass%, further preferably 50 to 96 mass%, and particularly preferably 70 to 95 mass%. By setting the content of the EVA (A) in the above range, a resin composition having particularly excellent thermal stability can be obtained.
[0027] <Saponified EVA with an Ethylene Content of More than 60 mol% (B)> The saponified EVA having an ethylene content of more than 60 mol% (B) used in the present resin composition is a saponified EVA, and is obtained by saponifying the vinyl acetate component of EVA having an ethylene content of more than 60 mol%.
[0028] The saponified EVA (B) having an ethylene content of more than 60 mol% (hereinafter referred to as "high ethylene saponified EVA (B)") is polymerized by any known polymerization method, such as solution polymerization, suspension polymerization, emulsion polymerization, etc., and the copolymer can be saponified by a known method. The high ethylene saponified EVA (B) may be modified as necessary.
[0029] The ethylene content of the high ethylene EVA saponification product (B) may be more than 60 mol%, and is usually 98 mol% or less, more preferably 75 to 95 mol%, and particularly preferably 80 to 95 mol%. By having the ethylene content within the above range, the effects of the present invention (thermal stability and coloring inhibition) tend to be more effectively obtained.
[0030] The saponification degree of the high ethylene EVA saponification product (B) is usually 20 mol% or more, more preferably 40 to 99.5 mol%, particularly preferably 80 to 99 mol%. That is, when the saponification degree is within the above range, the effects of the present invention (thermal stability, etc.) tend to be more effectively obtained.
[0031] The melt flow rate (MFR) (190°C, load 2160 g) of the above-mentioned high ethylene EVA saponification product (B) is usually 0.5 to 100 g / 10 min, more preferably 1 to 50 g / 10 min, and particularly preferably 2 to 30 g / 10 min, from the viewpoints of excellent dispersibility and excellent effects of the present invention. The MFR can be measured in accordance with JIS K7120.
[0032] The saponified ethylene-rich EVA (B) may be a modified product containing a carboxy group obtained by chemically bonding an unsaturated carboxylic acid or an anhydride thereof by addition reaction, graft reaction, or the like, within the scope of the present invention. The amount of modification is preferably 10 mol% or less, specifically. Examples of the unsaturated carboxylic acid or anhydride thereof include ethylenically unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, ethacrylic acid, and crotonic acid, and ethylenically unsaturated dicarboxylic acids such as fumaric acid, itaconic acid, citraconic acid, maleic acid, monomethyl maleate, monoethyl maleate, and maleic anhydride, and anhydrides and half esters thereof, among which maleic anhydride is preferably used.
[0033] The high ethylene EVA saponification product (B) may be used alone or in combination of two or more high ethylene content EVA saponification products differing in ethylene content, saponification degree, molecular weight, MFR, density, modifying group and modification amount thereof.
[0034] Moreover, the high ethylene EVA saponification product (B) used in the present resin composition preferably contains 14 carbon atoms.
[0035] The biobased degree of the high ethylene EVA saponification product (B) used in the present resin composition is usually 1 to 100%, preferably 5 to 100%, more preferably 10 to 100%, further preferably 40 to 100%, and particularly preferably 60 to 90%. By setting the biobased degree of the high ethylene EVA saponification product (B) within the above range, a resin composition having better thermal stability can be obtained.
[0036] The content of the high ethylene EVA saponification product (B) is 1 to 30 mass%, preferably 1.5 to 15 mass%, and particularly preferably 2 to 10 mass%, based on 100 mass% of the EVA (A). That is, when the ethylene content is equal to or less than the upper limit, the resin composition tends to have excellent coloring inhibition, and when the ethylene content is equal to or more than the lower limit, the appearance of the molded article obtained from the resin composition tends to be good.
[0037] The total amount [(A)+(B)] of the EVA (A) and the high ethylene EVA saponification product (B) in the entire resin composition is usually 70 to 100 mass% based on the entire resin composition.
[0038] The resin composition may contain thermoplastic resins other than the components (A) and (B), such as polyamide resins, polyester resins, and polyolefin resins, within a range that does not impair the effects of the present invention (for example, less than 30 mass% based on the total resin composition).
[0039] In addition, in the present resin composition, it is preferable to use, for example, hydrotalcites (C) and / or higher fatty acid metal salts (D) in combination with the above-mentioned EVA (A) and high ethylene EVA saponification product (B), since this improves the effect of suppressing foreign matter (dye deposits) generated by phase separation when a molded article is obtained using the present resin composition. Among these, hydrotalcites (C) are preferably used because they are particularly effective in suppressing discoloration when a regrind layer is obtained using recycled resin.
[0040] <Hydrotalcites (C)> Examples of the hydrotalcite compounds (C) include hydrotalcite solid solutions represented by the following general formula (1).
[0041] [Chemical Formula 1] [(M1 2+ ) y1 (M2 2+ ) y2 〕 1-x M x 3+ (OH)2A n- x / n ·mH2O ……(1) [In the formula, M1 2+ is at least one metal selected from Mg, Ca, Sr, and Ba, M2 2+ is at least one metal selected from Zn, Cd, Pb, and Sn, M x 3+ is a trivalent metal, A n- is an n-valent anion, and x, y1, y2, and m are positive numbers represented by 0 < x ≤ 0.5, 0.5 < y1 < 1, y1 + y2 = 1, and 0 ≤ m < 2, respectively.]
[0042] In the general formula (1), M1 2+ is preferably Mg or Ca, and M2 2+ is preferably Zn or Cd. Further, examples of M x 3+ include, for example, Al, Bi, In, Sb, B, Ga, Ti, etc. These can be used alone or in combination of two or more, and among them, Al is practical. Also, in the general formula (1), examples of A n- include, for example, CO3 2- , OH - , HCO3 - , salicylate ion, citrate ion, tartrate ion, NO3 - , I - , (OOC-COO) 2- , ClO 4- , CH3COO - , CO3 2- , (OOCHC=CHCOO) 2- , [Fe(CN)6] 4- etc. These can be used alone or in combination of two or more, and among them, CO32- OH - is particularly useful.
[0043] As a specific example of the hydrotalcite solid solution, [Mg 0.75 Zinc 0.25 ] 0.67 Al 0.33 (OH)2(CO3) 0.165 0.45H2O, [Mg 0.79 Zinc 0.21 ] 0.7 Al 0.3 (OH)2(CO3) 0.15 , [Mg 1 / 7 Ca 3 / 7 Zinc 3 / 7 ] 0.7 Al 0.3 (OH)2(OOCHC=CHCOO) 0.15 0.41H2O, [Mg 6 / 7 CD 1 / 7 ] 0.7 Al 0.3 (OH)2(CH3COO) 0.3 0.34H2O, [Mg 5 / 7 Pd 2 / 7 ] 0.7 Al 0.30 (OH)2(CO3) 0.15 0.52H2O, [Mg 0.74 Zinc 0.26 ] 0.68 Al 0.32 (OH)2(CO3) 0.16 , [Mg 0.56 Zinc 0.44 ] 0.68 Al 0.32 (OH)2(CO3) 0.16 0.2H2O, [Mg 0.81 Zinc 0.19 ] 0.74 Al 0.26 (OH)2(CO3) 0.13 , [Mg 0.75 Zinc 0.25 ] 0.8 Al 0.20 (OH)2(CO3) 0.10 0.16H2O, [Mg 0.71 Zinc 0.29 ] 0.7 Al 0.30(OH)2(NO3) 0.30 , [Mg 0.71 Zinc 0.29 ] 0.7 Al 0.30 (OH)2(OOCHC=CHCOO) 0.15 , [Mg 0.14 Ca 0.57 Zinc 0.28 ] 0.7 Al 0.30 (OH) 2.3 0.25H2O, among which [Mg 0.75 Zinc 0.25 ] 0.67 Al 0.33 (OH)2(CO3) 0.165 0.45H2O, [Mg 0.79 Zinc 0.21 ] 0.7 Al 0.3 (OH)2(CO3) 0.15 , [Mg 6 / 7 CD 1 / 7 ] 0.7 Al 0.3 (OH)2(CH3COO) 0.3 0.34H2O, [Mg 5 / 7 Pd 2 / 7 ] 0.7 Al 0.30 (OH))2(CO3) 0.15 0.52H2O etc.
[0044] Other examples of the hydrotalcites (C) include compounds represented by the following general formula (2).
[0045] [Case 2] M i Al j (OH) 2i+3j-2z (E) z aH2O ……(2) [In the formula, M is Mg, Ca, or Zn, E is CO3 or HPO4, i, j, and z are positive numbers, and a is 0 or a positive number.]
[0046] Specific examples of the compound represented by the above general formula (2) include Mg 4.5 Al2(OH) 13CO3·3.5H2O, Mg5Al2(OH) 14 CO3·4H2O,Mg6Al2(OH) 16 CO3·4H2O, Mg8Al2(OH) 20 CO3·5H2O,Mg 10 Al2(OH) 22 (CO3)2·4H2O, Mg6Al2(OH) 16 HPO4·4H2O, Ca6Al2(OH) 16 CO3·4H2O, Zn6Al6(OH) 16 CO3·4H2O, etc. In addition, the same effect can be expected even if the chemical formula is not clearly indicated, for example, a part of OH in Mg2Al(OH)9·3H2O is replaced by CO3 or HPO4, or even if the crystal water is removed (a=0). In particular, among these, a compound in which M is Mg and E is CO3 is preferably used because it effectively suppresses deterioration of appearance due to coloring caused by phase separation and phase-separated foreign matter (so-called eye resin) caused by phase separation, as well as molding stability.
[0047] The particle size of the hydrotalcites (C) is, for example, usually 10 μm or less, more preferably 5 μm or less, and particularly preferably 1 μm or less. That is, when the average particle size is equal to or less than the upper limit, the effect of the present invention tends to be more effectively obtained. The average particle size here is a value measured by the LUZEX method.
[0048] Among the above hydrotalcites (C), it is particularly preferable to use the hydrotalcite solid solution represented by the general formula (1) above, because of its high molding stability, phase separation foreign matter (dye deposits) suppression effect, and coloration suppression effect.
[0049] When the hydrotalcites (C) are used, their content is not particularly limited, but is preferably 0.5 to 30 mass%, more preferably 1 to 20 mass%, and even more preferably 2 to 10 mass%, relative to 100 mass% of the EVA (A). When the content is equal to or more than the lower limit, molding stability and the effect of suppressing foreign matter and coloring tend to be good, and when the content is equal to or less than the upper limit, the appearance of the molded product tends to be good, and the effect of suppressing coloring and mechanical properties tend to be excellent.
[0050] <Higher fatty acid metal salts (D)> Examples of the higher fatty acid metal salt (D) include metal salts of organic acids having 8 or more carbon atoms (more preferably 12 to 30 carbon atoms, particularly preferably 14 to 22 carbon atoms), such as alkali metal salts of lithium, sodium, potassium, etc., alkaline earth metal salts of magnesium, calcium, barium, etc., and transition metal salts of zinc, copper, cobalt, iron, manganese, etc. Among these, from the viewpoints of molding stability and the effect of suppressing phase-separated foreign matter (eye gunk) and coloration, alkaline earth metal salts and transition metal salts of higher fatty acids having 14 to 22 carbon atoms are preferred, and magnesium, calcium, and zinc salts of stearic acid, hydroxystearic acid, oleic acid, and lauric acid are particularly preferred.
[0051] When the higher fatty acid metal salt (D) is used, its content is not particularly limited, but is preferably 0.5 to 30 mass%, more preferably 1 to 20 mass%, and even more preferably 2 to 10 mass% relative to 100 mass% of the EVA (A). When the content is equal to or more than the lower limit, molding stability and an effect of suppressing foreign matter and coloring tend to be easily obtained, and when the content is equal to or less than the upper limit, the appearance of the obtained molded product tends to be good, and the effect of suppressing coloring and mechanical properties tend to be excellent.
[0052] When the hydrotalcites (C) and the higher fatty acid metal salt (D) are used in combination, the respective contents are preferably within the above ranges.
[0053] Furthermore, in the present resin composition, a titanium compound (E) can be used together with the above-mentioned EVA (A) and high ethylene EVA saponification product (B). The titanium compound (E) is used as a pigment or is contained in the recovered pulverized material, but the incorporation of such a titanium compound (E) tends to decrease the thermal stability of the resin composition. In the present resin composition, even when the titanium compound (E) is contained, the effect of improving the thermal stability can be obtained, and at the same time, the present resin composition has even better coloring inhibition properties.
[0054] <Titanium Compounds (E)> Examples of the titanium compound (E) include inorganic titanium compounds and organic titanium compounds. The titanium compounds may be used alone or in combination of two or more. Among them, inorganic titanium compounds are preferred.
[0055] Examples of the inorganic titanium compound include titanium oxide, titanium hydroxide, titanium chloride, and inorganic salts of titanium. Examples of the titanium oxide include titanium oxide (II), titanium oxide (III), titanium oxide (IV), and titanium suboxide. Examples of the titanium hydroxide include titanium(I) hydroxide and titanium(II) hydroxide. Examples of the titanium chloride include titanium(I) chloride, titanium(II) chloride, etc. Examples of the inorganic salts of titanium include titanium phosphate, titanium sulfate, etc. Among these, titanium oxide is preferred, titanium(IV) oxide is more preferred, and rutile-type titanium(IV) oxide is particularly preferred.
[0056] Examples of the organic titanium compound include titanium carboxylates such as titanium acetate, titanium butyrate, and titanium stearate.
[0057] In addition, the above titanium compound (E) may exist in the resin composition as a titanium compound, or may exist in an ionized state or in the form of a complex interacting with a resin component or other ligands.
[0058] When the titanium compound (E) is used, its average particle size is usually from 0.001 to 100 μm, preferably from 0.01 to 50 μm, and more preferably from 0.015 to 20 μm.
[0059] When the titanium compound (E) is used, its content in terms of metal is preferably 1 to 20 mass %, more preferably 1 to 15 mass %, still more preferably 1 to 10 mass %, and particularly preferably 1 to 8 mass %, based on the total mass of the resin composition.
[0060] The content of the titanium compound (E) calculated as metal can be quantified by weighing the resin composition into a platinum crucible, incinerating it using a burner and an electric furnace, decomposing the incinerated product by heating with nitric acid and hydrofluoric acid, treating it with a mixed acid of dilute nitric acid and dilute hydrofluoric acid, and measuring the titanium in the constant volume solution obtained by constant volume measurement using an ICP mass spectrometer (Agilent 8800, manufactured by Agilent Technologies).
[0061] <Other ingredients> In addition to the above-mentioned EVA (A), high ethylene EVA saponification product (B), hydrotalcites (C), higher fatty acid metal salts (D), and titanium compounds (E), resins other than EVA (A) and high ethylene EVA saponification product (B) (e.g., polyolefin resins and other types of resins) and optional additives (hereinafter, these are referred to as "other components") may be blended into the resin composition according to various purposes within a range that does not significantly impair the effects of the present invention. Only one type of other component may be used, or two or more types may be used in any combination and ratio.
[0062] Examples of the additives include lubricants, plasticizers, heat stabilizers, light stabilizers, ultraviolet absorbers, antioxidants, crystal nucleating agents, colorants, antistatic agents, surfactants, antibacterial agents, drying agents, oxygen absorbers, and antiblocking agents.
[0063] Among the above additives, it is particularly preferable to use an antioxidant in combination, since this has the effect of reducing thermal deterioration of the present resin composition.
[0064] <Antioxidants> Examples of the antioxidant include the following, and at least one of them can be selected. Hindered phenol compounds: dibutylhydroxytoluene, 2,5-di-t-butylhydroquinone, 2,6-di-t-butyl-p-cresol, 4,4'-thiobis-(6-t-butylphenol), 2,2'-methylene-bis(4-methyl-6-t-butylphenol), tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane, N,N'-hexamethylene-bis(3,5-di-t-butyl-4'-hydroxy-hydrocinnamamide), 1,3,5-trimethyl-2,4,6-tris(3 ,5-di-t-butyl-4-hydroxybenzyl)benzene, pentaerythritol-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, triethylene glycol-bis[3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate], 1,6-hexanediol-bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], 2,4-bis-(n-octylthio)-6-(4-hydroxy-3,5-di-t-butylanilino)-1,3,5-triazine, 2,2-thio -Diethylene bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 3,5-di-t-butyl-4-hydroxy-benzylphosphonate-diethyl ester, bis(3,5-di-t-butyl-4-hydroxybenzylphosphonate ethyl)calcium, tris-(3,5-di-t-butyl-4-hydroxybenzyl)-isocyanurate, 2,4-bis[(octylthio)methyl]-o-cresol, isooctyl-3-(3,5- Di-t-butyl-4-hydroxyphenyl)propionate, n-octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2-t-butyl-6-(3-t-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate, 2-[1-(2-hydroxy-3,5-di-t-pentylphenyl)ethyl]-4,6-di-t-pentylphenyl acrylate, 4,4'-butylidenebis(3-methyl-6-t-butylphenol), 4,4'-thiobis(3-methyl-6-t-butylphenol), 3,9-Bis{2-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)-propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro(5·5)undecane, etc.; Phosphite compounds: triaryl phosphites such as triphenyl phosphite, tris(p-nonylphenyl)phosphite, tris(2,4-di-t-butylphenyl)phosphite, etc.; monoalkyl diphenyl phosphites such as diphenyl isooctyl phosphite, diphenyl isodecyl phosphite, etc.; dialkyl monophenyl phosphites such as phenyl diisooctyl phosphite, phenyl diisodecyl phosphite, etc.; trialkyl phosphites such as triisooctyl phosphite, tristearyl phosphite, etc.; bis(2,4-di-t-butylphenyl)pentaerythritol-diphosphite, etc.; Thioether compounds: pentaerythritol-tetrakis-(β-laurylthiopropionate), tetrakis[methylene-3-(dodecylthio)propionate]methane, bis[2-methyl-4-{3-n-alkylthiopropionyloxy}-5-t-butylphenyl]sulfide, dilauryl-3,3'-thiodipropionate, dimystyryl-3,3'-thiodipropionate, distearyl-3,3'-thiodipropionate, pentaerythritol-tetrakis(3-laurylthiopropionate), ditridecyl-3,3'-thiodipropionate, 2-mercaptobenzimidazole, etc.; Hindered amine compounds: Dimethyl succinate·1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylbenzyl polycondensate, poly{[6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidyl)imino]hexamethylene[(2,2,6,6-tetramethyl-4-piperidyl)imino]}, N,N'-bis(3-aminopropyl)ethylene Diamine·2,4-bis[N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidyl)amino]-6-chloro-1,3,5-triazine condensate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate, 2-(3,5-di-t-butyl-4-hydroxybenzyl)-2-n-butylmalonate bis(1,2,2,6,6-pentamethyl-4-piperidyl) and the like; Benzotriazole compounds: 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]-2H-benzotriazole, 2-(3,5-di-t-butyl-2-hydroxyphenyl)benzotriazole, 2-(3-t-butyl-5-methyl-2-hydroxyphenyl)-5-chlorobenzotriazole, 2-(3,5-di-t-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole, 2-(3 ,5-di-t-amyl-2-hydroxyphenyl)benzotriazole, 2-(2'-hydroxy-5'-t-octylphenyl)benzotriazole, methyl-3-[3-t-butyl-5-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]propionate-polyethylene glycol condensate, hydroxyphenylbenzotriazole derivatives, 2-[2-hydroxy-3-(3,4,5,6-tetra-hydrophthalimido-methyl)-5-methylphenyl]benzotriazole, etc.; Benzophenone compounds: 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octyloxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, etc.; These antioxidants may be in any form, such as powder, granules, liquid, paste, emulsion, etc.
[0065] Among the above antioxidants, hindered phenol antioxidants are preferred, and in particular, pentaerythritol-tetrakis-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate and octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate are preferably used since they have an excellent effect of reducing the thermal degradation of the resin composition and do not inhibit the effect of the present invention (suppression of discoloration of the regrind layer).
[0066] When the antioxidant is used, the content is, for example, usually 0.001 to 10 mass%, preferably 0.01 to 5 mass%, and particularly preferably 0.05 to 1 mass% relative to 100 mass% of the EVA (A). By making the content of the antioxidant equal to or more than the lower limit, the thermal deterioration of the present resin composition tends to be reduced, and by making the content equal to or less than the upper limit, the appearance of the obtained molded article tends to be good, and the discoloration prevention effect and mechanical properties tend to be good.
[0067] When the present resin composition contains the above-mentioned "other components", the total content thereof is usually 30 mass % or less, preferably 20 mass % or less, and more preferably 10 mass % or less, relative to the present resin composition.
[0068] [Method of producing resin composition] The resin composition can be produced by mixing the essential components EVA (A) and high ethylene EVA saponification product (B), hydrotalcites (C), higher fatty acid metal salts (D), titanium compounds (E), and other components, which are used as necessary. Examples of the mixing method include known methods such as a dry blend method, a melt mixing method in which a compound is obtained using a single-screw extruder or a twin-screw extruder, a solution mixing method, and an impregnation method, and these methods can be used in any combination.
[0069] [Resin composition] The resin composition thus obtained is less susceptible to decomposition at high temperatures, has excellent thermal stability, and is also excellent in coloration inhibition, compared to conventional resin compositions in which the EVA (A) and / or the saponified EVA (B) does not contain carbon-14.
[0070] The melt flow rate (MFR) of the present resin composition (190° C., load 2160 g) is usually from 0.1 to 50 g / 10 min, preferably from 0.5 to 30 g / 10 min, and particularly preferably from 2 to 10 g / 10 min. The MFR can be measured in accordance with JIS K7120.
[0071] The water content of the present resin composition is usually from 0.01 to 0.5% by mass, preferably from 0.02 to 0.35% by mass, and particularly preferably from 0.05 to 0.3% by mass.
[0072] The water content of the resin composition in the present invention is measured and calculated by the following method. The mass (W1) of the resin composition before drying is weighed on an electronic balance, dried in a hot air dryer at 150°C for 5 hours, and then cooled in a desiccator for 30 minutes, after which the mass (W2) is weighed and calculated using the following formula. Moisture content (mass%)=[(W1-W2) / W1]×100
[0073] The present resin composition is prepared as a resin composition in various forms, such as pellets or powder, and is provided as a material for various molded bodies and multilayer structures. As described above, since the present resin composition has excellent thermal stability and coloration suppression properties, a molded body using the present resin composition or a multilayer structure having a layer using the present resin composition has the advantage that deterioration in quality, such as thermal degradation and coloration, is small even when the composition is recycled.
[0074] Furthermore, the present resin composition can be suitably used as a recovery aid (hereinafter referred to as "the present recovery aid") for resin recovery materials containing polyolefin resin and EVOH (ethylene content of 60 mol% or less) (for example, recovered materials such as scraps of laminates containing a polyolefin resin layer and an EVOH layer).
[0075] [Resin composition for recovery aid] When the present resin composition is used as a resin composition for a recovery aid, the content of the present resin composition is preferably 50 mass% or more, more preferably 70 mass% or more, even more preferably 90 mass% or more, and particularly preferably 100 mass%, based on the entire resin composition for a recovery aid. The higher the content, the easier it tends to be to obtain the effect as a recovery aid. In this specification, the recovery aid refers to an additive that is blended when mixing or otherwise processing a recovered resin material containing a polyolefin resin and EVOH (for example, a recovered material obtained by recovering scraps of a laminate containing a polyolefin resin layer and an EVOH layer), and is also sometimes referred to as a compatibilizer or a recycling aid. The present recovery aid is prepared by forming the present recovery aid resin composition into a powder form.
[0076] [Molded body] A molded article according to one embodiment of the present invention (hereinafter, referred to as the present molded article) is obtained by molding the present resin composition.
[0077] Examples of the shape of the present molded product include films, sheets, tapes, cups, trays, tubes, bottles, pipes, filaments, irregular cross-section extrudates, and various irregularly shaped products.
[0078] The molding method for obtaining the molded article is not particularly limited, and any molding method applicable to general resin compositions can be used, such as extrusion molding, blow molding, injection molding, thermoforming, etc.
[0079] [Multilayer structure] A multilayer structure according to one embodiment of the present invention (hereinafter, referred to as "the present multilayer structure") has a layer containing the present resin composition. The present multilayer structure can be provided with additional strength or other functions by being laminated with another substrate containing as a main component a thermoplastic resin other than the present resin composition. Incidentally, the term "mainly composed of a thermoplastic resin" means a component that has a significant effect on the characteristics of the substrate, and the content of the thermoplastic resin in the substrate is 50 mass % or more, preferably 55 mass % or more, more preferably 60 mass % or more, and even more preferably 70 mass % or more, and may be 100 mass %.
[0080] The multilayer structure may have a layer (regrind layer) using a mixture (hereinafter referred to as "resin composition for forming a regrind layer") containing the resin composition (the recovery aid) of the recovered laminate including, for example, a polyolefin resin layer and an EVOH layer. Such a multilayer structure having a regrind layer will be described below.
[0081] The recycled laminates containing a polyolefin resin layer and an EVOH layer used to obtain the above-mentioned regrind layer are scraps, unnecessary parts such as ends of the product, defective products, or waste after the molded body has been used for various purposes, which are collected during the production process. When these recycled materials are reused as a regrind layer, the present resin composition is used as a recycling aid.
[0082] In addition, the recovered material used for recycling is generally scraps related to one molded body, but scraps related to two or more types of molded bodies may be used as the recovered material.
[0083] The regrind layer can be obtained, for example, by blending the present resin composition with the recycled material and melt molding the mixture to obtain a molded product, etc. The method of blending the present resin composition with the recycled material and melt molding the mixture will be described below.
[0084] First, in order to subject the recovered laminate to melt molding again using an extruder or the like, it is preferable to pulverize the recovered laminate.
[0085] The above-mentioned recovered material can be pulverized by using a known pulverizer. The shape and particle size of the pulverized product are usually 0.25 to 0.85 g / mL, more preferably 0.3 to 0.7 g / mL, and particularly preferably 0.35 to 0.6 g / mL, as measured in accordance with the "5.3 Apparent Density" test method of JIS-K6891. When the apparent density is equal to or greater than the lower limit, the dispersion of EVOH in the regrind layer is good, and the melt moldability and mechanical properties of the regrind layer of the obtained molded product tend to be excellent. When the apparent density is equal to or less than the upper limit, the supply in the extruder is stable, and the melt moldability of the regrind layer of the molded product tends to be improved.
[0086] This apparent density can be controlled by arbitrarily adjusting the shape of the grinding blade of the grinding machine, the rotation speed of the grinding blade, the grinding processing speed, the size of the openings of the mesh used, and the like.
[0087] Here, the content of EVOH in the above-mentioned recovered material is usually 0.1 to 30% by mass based on the total mass of the recovered material, and in order to particularly exhibit the effect of the present resin composition as a recycling aid, it is further preferably set to 0.3 to 25% by mass, particularly 0.5 to 20% by mass. In the present invention, the improving effect is exhibited for any recovered material content, but the improving effect is particularly exhibited within the above range.
[0088] The content of EVOH in the above-mentioned recycled material depends on the thickness ratio of the EVOH layer in the laminate, and if the content of EVOH is too low, the content may be adjusted by mixing an appropriate amount of a similar or different unused EVOH as necessary. Conversely, if the content of EVOH is too high, it is also practically preferable to adjust the content by mixing an appropriate amount of a same or different unused polyolefin resin.
[0089] Next, the resin composition is blended with the pulverized recycled material. As the blending method, for example, a known mixer such as a rocking mixer, a ribbon blender, a super mixer, or a line mixer can be used.
[0090] The amount of the resin composition to be blended with respect to the above-mentioned recycled material depends on the layer structure of the recycled material, the type of polyolefin resin, the content of EVOH, the container form, the use of the product, the required physical properties, etc., and cannot be generally determined. However, the ratio of the recycled material (x) to the resin composition (y) [(x) / (y)] is usually (x) / (y)=99.5 / 0.5 to 60 / 40, more preferably 99 / 1 to 70 / 30, and particularly preferably 98 / 2 to 90 / 10, in terms of mass ratio. By blending the resin composition in an amount equal to or greater than the lower limit, the effect of the resin composition as a recycling aid tends to be more easily obtained. In addition, by being equal to or less than the upper limit, the appearance of the obtained molded product tends to be good, odor during molding is suppressed, and mechanical properties tend to be improved.
[0091] In this manner, a mixture of the recycled material and the present resin composition (resin composition for forming the regrind layer) is obtained.
[0092] The present multilayer structure having at least one regrind layer can be obtained by using the above resin composition. The present multilayer structure having a regrind layer is generally preferably a multilayer structure containing a polyolefin resin layer, an EVOH layer, and an adhesive resin layer as necessary, in addition to the regrind layer. Note that the polyolefin resin layer, the EVOH layer, and the adhesive resin layer do not contain EVA (A).
[0093] Examples of the layer configuration of the multilayer structure containing a regrind layer include polyolefin resin layer / regrind layer / adhesive resin layer / EVOH layer, polyolefin resin layer / regrind layer / adhesive resin layer / EVOH layer / adhesive resin layer / polyolefin resin layer, polyolefin resin layer / regrind layer / adhesive resin layer / EVOH layer / adhesive resin layer / regrind layer / polyolefin resin layer, and further regrind layer / EVOH layer, regrind layer / adhesive resin layer / EVOH layer, regrind layer / adhesive resin layer / EVOH layer / adhesive resin layer / EVOH layer / adhesive resin layer / polyolefin resin layer, regrind layer / adhesive resin layer / EVOH layer / adhesive resin layer / regrind layer / polyolefin resin layer, polyolefin resin layer / adhesive resin layer / EVOH layer / regrind layer / EVOH layer / adhesive resin layer / polyolefin resin layer, and the like.
[0094] The thickness of each layer of the multilayer structure containing a regrind layer depends on the layer structure, the type of polyolefin resin, the application, the container form, the required physical properties, etc., and cannot be generally determined, but the regrind layer is usually 5 to 5000 μm, and more preferably 30 to 1000 μm. The EVOH layer is usually 5 to 500 μm, and more preferably 10 to 200 μm. The polyolefin resin layer is usually 5 to 5000 μm, and more preferably 30 to 1000 μm. In this case, when an adhesive resin layer is present, the adhesive resin layer is usually 5 to 400 μm, and more preferably 10 to 150 μm.
[0095] The thickness ratio of the regrind layer to the polyolefin resin layer is usually 1 / 5 to 10 / 1, and preferably 1 / 2 to 5 / 1. The thickness ratio of the regrind layer to the EVOH layer is usually 1 / 1 to 100 / 1, and preferably 5 / 1 to 20 / 1.
[0096] The regrind layer-containing multilayer structure can be produced, for example, by the same method as that for forming the laminate using the same resin as that for the laminate to be recycled. Specifically, the regrind layer-containing multilayer structure can be produced by the following method using the polyolefin resin used in the polyolefin resin layer of the laminate to be recycled, the EVOH used in the EVOH layer, and the adhesive resin used in the adhesive resin layer.
[0097] Examples of methods for obtaining the multilayer structure include a method of melt extrusion laminating a resin composition onto an EVOH film, sheet, etc., a method of melt extrusion laminating a resin composition onto a substrate consisting of a polyolefin layer, a method of co-extruding an EVOH or polyolefin resin with a resin composition, and a method of dry laminating an EVOH or polyolefin resin film, sheet, etc. with a resin composition film, sheet, etc. using an adhesive such as an organic titanium compound, an isocyanate compound, a polyester compound, a polyurethane compound, etc. The melt molding temperature during the above melt extrusion is usually in the range of 150 to 300°C.
[0098] The above-mentioned regrind layer-containing multilayer structure can be used as it is for various shapes, but it can also be subjected to a heat stretching treatment in order to further improve the physical properties of this laminate and to mold it into any desired container shape.
[0099] The heat stretching treatment as used herein means an operation of forming a thermally uniformly heated film, sheet or parison-like multilayer structure into a shape such as a cup, tray, tube or bottle by means of a chuck, plug, vacuum force, compressed air force, blow or the like.
[0100] Examples of the stretching method in the above-mentioned heat stretching treatment include roll stretching, tenter stretching, tubular stretching, stretch blowing, vacuum forming, pressure forming, vacuum pressure forming, etc. In the case of biaxial stretching, either simultaneous biaxial stretching or sequential biaxial stretching can be adopted. The stretching temperature is usually 60 to 170°C, and more preferably about 80 to 160°C. Either uniaxial stretching or biaxial stretching can be used, and the higher the stretching ratio, the better the physical properties will be, and a stretched molded product with excellent gas barrier properties will be obtained without pinholes, cracks, stretching unevenness, thickness deviation, delamination, etc. during stretching.
[0101] In the present multilayer structure, the recycled material used for the regrind layer may also have a regrind layer therein, and a laminate having at least one regrind layer containing such recycled material can be molded by the same method using the same type of resin as the recycled material as a raw material. That is, a laminate having at least one regrind layer (recycled product) is manufactured using a resin composition obtained from the recycled material, and the recycled material of the molded product may be used again as the regrind layer of a similar laminate (recycled product).
[0102] In addition, as other forms of the present multilayer structure, [1] recycled materials of laminates having multiple different types of polyolefin resin layers or multiple different types of EVOH layers, and / or recycled materials of multiple different types of laminates can be used in the same regrind layer, or [2] recycled materials can be used in the regrind layer of a laminate having a type of polyolefin resin and EVOH different from the polyolefin resin and EVOH contained in the recycled materials.
[0103] In addition, in order to improve moldability, physical properties, and the like, antioxidants, heat stabilizers, light stabilizers, lubricants, antistatic agents, crystal nucleating agents, plasticizers, colorants, UV absorbers, surfactants, antibacterial agents, desiccants, oxygen absorbers, antiblocking agents, slip agents, inorganic or organic fillers, and the like can be added to each layer of the present multilayer structure, provided that the effects of the present invention are not impaired.
[0104] Furthermore, the present multilayer structure may be subjected to processes such as heat treatment, cooling treatment, rolling treatment, printing treatment, dry lamination treatment, solution or melt coating treatment, bag making, deep drawing, box processing, tube processing, and split processing, as required.
[0105] The multilayer structure, whether recycled or re-recycled, is useful as a container for various purposes such as general foods, seasonings such as mayonnaise and dressings, fermented foods such as miso, oily foods such as salad oil, soups, beverages, cosmetics, medicines, detergents, fragrances, industrial chemicals, pesticides, and fuels, but is particularly useful as bottle-shaped or tube-shaped containers for semi-solid foods and seasonings such as mayonnaise, ketchup, sauces, miso, wasabi, mustard, and sauces for grilled meat, and liquid beverages and seasonings such as salad oil, mirin, sake, beer, wine, juice, black tea, sports drinks, mineral water, and milk; cup-shaped containers for semi-solid foods and seasonings such as fruit, jelly, pudding, yogurt, mayonnaise, miso, processed rice, cooked foods, and soups; and tray-shaped containers for raw meat, processed meat products (ham, bacon, sausages, and the like), cooked rice, and pet food. EXAMPLES
[0106] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not deviate from the gist of the present invention. In addition, unless otherwise specified, "parts" and "%" below are based on mass. Prior to the examples, the following components were prepared:
[0107] [EVA(A)] Carbon-14-containing EVA (A1): EVA derived from biomass resources (Braskem, SVT2145R), ethylene content 95 mol%, vinyl acetate mass content 14%, MFR (190°C, load 2160 g) 2.1 g / 10 min, bio-based content 88% Petroleum-derived EVA (A2): EVA derived from petroleum raw materials (Ultrathene 630, manufactured by Tosoh Corporation), ethylene content 95 mol%, vinyl acetate content by mass 15%, MFR (190°C, load 2160 g) 1.5 g / 10 min, density 0.936 g / cm 3 [Saponified EVA (B)] Saponified EVA (B1): Saponified EVA derived from petroleum raw materials (Tosoh Corporation, Mersen H0051K), ethylene content 89 mol%, saponification degree 99 mol%, MFR (190°C, load 2160 g) 6.5 g / 10 min [Hydrotalcites (C)] Hydrotalcites (C1): Hydrotalcite solid solution (Kyowa Chemical Industry Co., Ltd., ZHT-4A) [Higher fatty acid metal salts (D)] Higher fatty acid metal salt (D1): Calcium stearate (Nissan Calcium Stearate S, manufactured by Nippon Oil & Fats Co., Ltd.) [Titanium compounds (E)] Titanium compound (E1): Titanium oxide (manufactured by Wako Pure Chemical Industries, Ltd.) [Antioxidants] Pentaerythritol tetrakis(3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate) (Ciba Specialty Chemicals, Irganox 1010)
[0108] <Example 1> 85 parts of carbon-14-containing EVA (A1), 5 parts of EVA saponification product (B1), 5 parts of hydrotalcites (C1), 5 parts of higher fatty acid metal salt (D1), 0.05 parts of antioxidant, and 5 parts of titanium compound (E1) were mixed together by dry blending, and then fed to a twin-screw kneader at a rate of 8 kg / hour using a mass feeder, and then strand-cut with a drum pelletizer to prepare a pellet-shaped resin composition. The kneading conditions were as follows: [Mixing conditions] Twin screw extruder: Diameter 20mm L / D=48 (Toshiba Machine Co., Ltd.) ·Extruder setting temperature (℃): C1 / C2 / C3 / C4 / C5 / C6 / H=120 / 150 / 160 / 160 / 170 / 170 / 170 Screw speed: 250 rpm -Reel speed: 12m / min
[0109] <Examples 2 to 4, Comparative Examples 1 and 2> Resin compositions of Examples 2 to 4 and Comparative Examples 1 and 2 were prepared in the same manner as in Example 1, except that the types and amounts of each component were changed as shown in Table 1 below.
[0110] The following thermal stability evaluation and coloration inhibition evaluation were carried out using the obtained resin compositions of Examples 1 to 4 and Comparative Examples 1 and 2. The results are shown in Table 1 below.
[0111] [Thermal stability evaluation (10% decrease temperature)] Using 5 mg of the obtained pellet-like resin composition, the temperature at which the resin composition had decreased to 95% of the mass before measurement (10% decrease temperature) was measured using a thermogravimetric analyzer (Perkin Elmer, Pyris 1 TGA) under conditions of a nitrogen atmosphere, an air flow rate of 20 mL / min, and a temperature range of 30 to 550° C. The higher this value, the slower the decomposition of the resin composition is, and the better the thermal stability of the resin composition is. In addition, the evaluation was carried out based on the following criteria. A(excellent): 10% decrease in temperature is 370.0℃ or more B (very good): 10% decrease in temperature is between 367.5℃ and 370.0℃ C(goodpoor): 10% decrease in temperature is between 362.5℃ and 367.5℃ D(poor): 10% decrease in temperature is less than 362.5℃
[0112] [Coloration suppression evaluation (YI value ratio)] The pellet-like resin composition was pulverized at 650 rpm in a pulverizer (SKR16-240, manufactured by Sometani Sangyo Co., Ltd.) to obtain pulverized material of 1 to 5 mm square. The obtained pulverized material was packed into a cylinder having an inner diameter of 32 mm and a height of 30 mm, and in this state, the yellow index (YI value) before heating was measured using a spectrophotometer (manufactured by Nippon Denshoku Industries Co., Ltd.). The crushed product was also heat-treated in an oven under air at 60°C for 3 days, and the YI value after heating was measured in the same manner. The ratio of the YI value after heating to the YI value before heating was calculated. The larger this value, the more yellow the resin composition was colored after heating. The evaluation was carried out based on the following criteria. A(excellent): YI value ratio is 1.0 or less B (very good): YI value ratio is over 1.0 and 3.5 or less. C(good): YI value ratio is over 3.5 and 5.0 or less D(poor): YI value ratio exceeds 5.0
[0113] [Table 1]
[0114] From the results in Table 1, it can be seen that the resin compositions of Examples 1 to 4, which use the carbon-14-containing EVA (A1) as the EVA, have improved thermal stability compared to Comparative Examples 1 and 2, which use the petroleum-derived EVA (A2). In addition, a comparison between Example 2 and Comparative Example 1 shows that the use of the carbon-14-containing EVA (A1) also improves coloration inhibition. The reason for this is that the carbon-14 ( 14 C)-containing EVA has stronger binding energy due to the primary isotope effect, which slows decomposition and increases thermal stability, and is thought to provide a synergistic effect with hydrotalcites (C1) and higher fatty acid metal salts (D1). It is also clear that the effects of the products of Examples 1 to 4, that is, excellent thermal stability and coloration inhibition, can be obtained in the same manner even if the blending ratio and types of each component are changed. It is noted from Example 1 and Comparative Example 2 that when the resin composition contains a titanium compound (E1), the thermal stability and color inhibition are improved by using the carbon-14-containing EVA (A1) instead of the petroleum-derived EVA (A2), and furthermore, the color inhibition is excellent among the products of Examples 1 to 4. [Industrial Applicability]
[0115] The resin composition has higher thermal stability and coloring suppression than a resin composition using petroleum-derived EVA. Therefore, a molded body made of the resin composition and a multilayer structure having a layer containing the resin composition are useful as a packaging material for various packaging containers and food packaging. Furthermore, the resin composition is useful as a recovery aid for recovered resin products containing polyolefin resin and EVOH.
Claims
1. A resin composition containing an ethylene-vinyl acetate copolymer (A), The resin composition, wherein the ethylene-vinyl acetate copolymer (A) contains 14 carbon atoms.
2. A resin composition comprising an ethylene-vinyl acetate copolymer (A) and a saponified ethylene-vinyl acetate copolymer (B) having an ethylene content of more than 60 mol%, A resin composition, wherein the ethylene-vinyl acetate copolymer (A) and / or the saponified ethylene-vinyl acetate copolymer (B) contain 14 carbon atoms.
3. The resin composition according to claim 2, wherein the ethylene-vinyl acetate copolymer (A) contains 14 carbon atoms.
4. The resin composition according to claim 2, wherein the ethylene-vinyl acetate copolymer (A) and / or the saponified ethylene-vinyl acetate copolymer (B) having an ethylene content of more than 60 mol% has a biobased content of 1 to 100%.
5. 3. The resin composition according to claim 1, wherein the ethylene-vinyl acetate copolymer (A) has a bio-based content of 1 to 100%.
6. 3. The resin composition according to claim 1, wherein the ethylene-vinyl acetate copolymer (A) has a biobased content of 40 to 100%.
7. The resin composition according to claim 1 or 2, wherein the ethylene content of the ethylene-vinyl acetate copolymer (A) is 60 to 98 mol %.
8. The resin composition according to claim 1 or 2, further comprising a hydrotalcite (C).
9. The resin composition according to claim 1 or 2, further comprising a higher fatty acid metal salt (D).
10. The higher fatty acid metal salt (D) is a higher fatty acid calcium salt, a higher fatty acid magnesium salt and zinc salts of higher fatty acids.
11. The resin composition according to claim 1 or 2, further comprising a titanium compound (E).
12. The resin composition according to claim 11, wherein the titanium compound (E) is titanium oxide.
13. A resin composition for use as a recovery aid, comprising the resin composition according to claim 1 or 2.
14. Use of the resin composition according to claim 1 or 2 as a recovery aid.
15. A recovery aid comprising the resin composition according to claim 1 or 2.
16. A regrind layer comprising the recovery aid of claim 14.
17. A multi-layer structure comprising a regrind layer according to claim 16.
18. The multilayer structure according to claim 17, further comprising a layer containing a polyolefin resin (but not containing an ethylene-vinyl acetate copolymer (A)).
19. 20. The multilayer structure according to claim 18, further comprising an adhesive resin layer different from the regrind layer (but not including an ethylene-vinyl acetate copolymer (A)).
20. A package comprising the multi-layer structure of claim 17.
21. 20. A food package comprising the multi-layer structure of claim 17.
22. The method includes a step of mixing an ethylene-vinyl acetate copolymer (A) and a saponified ethylene-vinyl acetate copolymer (B) having an ethylene content of more than 60 mol%, The method for producing a recovery aid, wherein the ethylene-vinyl acetate copolymer (A) and / or the saponified ethylene-vinyl acetate copolymer (B) contain carbon-14.
Citation Information
Patent Citations
Polymer composition with low CO2 emissions and method for preparing same
JP2021536526A
Resin composition, molding resin composition prepared by using the same, laminates, and process for the production of laminates
WO2009041440A1
Cited By
Resin composition, compatibilizer, multilayer structure, method for producing resin composition, and method for producing multilayer structure
WO2026181925A1